Adjustment Level of Pupil Teachers: The Impact of Demographic Factors on the Adjustment Level of Pupil Teachers (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Adjustment is important for several other reasons also,failure to adjust leads to ineffective teaching and loss of educationalopportunities. Adjustment means regulating, adapting or settling in avariety of contexts. It is the behavioural process of balancing conflictingneeds, or needs against obstacles in the environment. Present study focuses onthe study of adjustment of pupil teachers and the influence of demographicfactors gender and residing area, stream of education and age on adjustment ofpupil teachers. Researcher collected data from the pupil teachers studying in secondary level teacher traininginstitutions of Haryana. Sample consists of 300 pupil teachers. Thetools used for data collection is Adjustment Inventory for College Students(AICS) by Sinha, A.K.P. and Singh, R.P. (1993). Findings of the study revealedthat there is no influence of gender, residing area, stream of education andage on adjustment of pupil teachers.